MAKNA RUMAH TRADISIONAL KUDUS - Anisa Anisa (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2005)
ABSTRACTPoespowardojo ( in Budihardjo, 1994) stated that there are two essencesof house for the residences. The former essence, house is a world where theresidences must develop theirselves. The later essence, house isa placewhich the residence must adapt to the local culture. So that, the meaning ofhouse has a close relation with the sicial, culture and economic backgroundof the owner.This research is focused on the ornaments of Kudus Traditional House,that right know slowly destroyed. The aim of this research is to get the meaningof the house, through discovering the residences value systems, physically ornon physically.There are several value systems found at Kudus traditional house, that is:hierarchy, status symbol, gender, sacral-profane, duniawi-ukhrowi, pingitanculture, collumn meaning, and tumpangsari. Those value systems have. veryclose relation and also form the meaning of Kudus traditional house.The main result of this research is that the meaning of a house is veryinfluenced by social and culture condition in Kudus, and also by the economicbackground of the owner.Keywords: Kudus traditional house, meaning, value system